ChemInform Abstract: Preparation of a Microsized Cerium Chloride‐Based Catalyst and Its Application in the Michael Addition of β‐Diketones to Vinyl Ketones. Issue 38 (10th September 2014) - Terent'ev, Alexander O.; Vil', Vera A.; Yaremenko, Ivan A.; Bityukov, Oleg V.; Levitsky, Dmitri O.; Chernyshev, Vladimir V.; Nikishin, Gennady I.; Fleury, Fabrice
Abstract The title catalyst is prepared by heating the commercially available CeCl3·(H2O)7.